WEB-SUPLEMEN SEBAGAI SARANA PEMBELAJARAN E-LEARNING ILMU PERPUSTAKAAN - Wahyuningsih, Sri Suharmini (Jurnal Pendidikan, 2012)
E-learning is a model of learning carried out through the utilization of information and communication technology services such as internet, video/audio conferencing, or CD-ROM. It is a technology-based learning design of computer networks known as the world wide web (www). The design was developed through designing learning materials under a multimedia package and was integrated in a full online interactivity. Any form of learning components such as teaching or evaluation materials were distributed to learners through a computer network (online), so that learners who attended the program must be an IT literate person. In its implementation, e-learning could be applied to various fields of science including library science. Librarians who do such work require the ability and expertise to cataloging, indexing and classification. Web-based learning material helped students understand those materials easily. E-learning merupakan model pembelajaran yang dilakukan melalui pemanfaatan informasi dan layanan teknologi komunikasi seperti internet, konferensi video/audio, atau CD-ROM. E-learning merupakan suatu desain pembelajaran berbasis teknologi jaringan komputer yang dikenal sebagai world wide web (www). Desain ini dikembangkan melalui rancangan materi pembelajaran berdasarkan suatu paket multimedia terintegrasi dalam interaktivitas online. Segala bentuk komponen pembelajaran seperti bahan pengajaran atau evaluasi dibagikan kepada peserta didik melalui jaringan komputer (online), sehingga peserta didik yang mengikuti program ini haruslah orang yang melek IT. Dalam pelaksanaannya, e-learning dapat diterapkan pada berbagai bidang ilmu pengetahuan termasuk ilmu perpustakaan. Pustakawan yang melakukan pekerjaan seperti ini membutuhkan kemampuan dan keahlian untuk katalogisasi, pengindeksan dan klasifikasi. Materi pembelajaran berbasis web membantu siswa belajar dengan mudah.